Dostoevsky's reflection on education: The Last letters - Loré, Michele (Formazione & insegnamento, 2022)
The article focuses on the pedagogical insights offered by Fyodor Dostoevsky’s Last letters, to be correlated with the narrative production. The result is a subtle sensitivity towards childhood and adolescence, whose specific problems stand out against the background of the European value crisis of the late Nineteenth century.